2015
DOI: 10.1002/jcb.25273
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Release From the Oviductal Epithelium Depends on Ca2+Influx Upon Activation of CB1 and TRPV1 by Anandamide

Abstract: The oviduct acts as a functional sperm reservoir in many mammalian species. Both binding and release of spermatozoa from the oviductal epithelium are mainly modulated by sperm capacitation. Several molecules from oviductal fluid are involved in the regulation of sperm function. Anandamide is a lipid mediator involved in reproductive physiology. Previously, we demonstrated that anandamide, through activation of the cannabinoid receptor type 1 (CB1), promotes sperm release from bovine oviductal epithelial cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…One report demonstrated that during peri-ovulatory period AEA induce bull sperm capacitation by activate CB1 and TRPV1 receptors, with the help of heparin, suggest effects of AEA may differ in different species [211]. AEA also regulates the sperm release from oviductal epithelia with the participation of NO · [212] and calcium [213]. Another report showed that the effects of AEA on human sperm motility were dependent on the reduction of sperm mitochondrial activity, and that it also inhibits capacitation-induced acrosome reaction [214].…”
Section: Different Pathways In Capacitationmentioning
confidence: 99%
“…One report demonstrated that during peri-ovulatory period AEA induce bull sperm capacitation by activate CB1 and TRPV1 receptors, with the help of heparin, suggest effects of AEA may differ in different species [211]. AEA also regulates the sperm release from oviductal epithelia with the participation of NO · [212] and calcium [213]. Another report showed that the effects of AEA on human sperm motility were dependent on the reduction of sperm mitochondrial activity, and that it also inhibits capacitation-induced acrosome reaction [214].…”
Section: Different Pathways In Capacitationmentioning
confidence: 99%
“…In our laboratory, we have developed an in vitro model to study the sperm-oviduct interaction in cattle [Gervasi et al, 2009[Gervasi et al, , 2015. In our laboratory, we have developed an in vitro model to study the sperm-oviduct interaction in cattle [Gervasi et al, 2009[Gervasi et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were performed using an in vitro model to evaluate the sperm-oviduct interaction developed previously in our laboratory [Gervasi et al, 2009[Gervasi et al, , 2015Osycka-Salut et al, 2012]. The presence of Fn in the apical region of epithelial cells suggests a possible participation of Fn in the binding to spermatozoa during the formation of the sperm reservoir.…”
Section: Participation Of Fn In the Sperm-oviduct Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that anandamide (AEA), an endocannabinoid synthesized by sperm and oviductal cells, activates TRPV1 and the ligand-receptor interaction occurs through a cytosolic binding site triggering an increase of intracellular Ca + concentration and/or activation of protein kinases (20). TRPV1 is expressed in mammalian spermatozoa and its activation is involved in the regulation of sperm oviduct interaction, sperm capacitation and acrosome reaction (21)(22)(23). On the other hand, sperm release from the oviductal reservoir depends on Ca + influx by activation of cannabinoid type migration toward a temperature gradient that was reduced by the addition of selective antagonists of TRPV1.…”
mentioning
confidence: 99%